Effect of Resonant Frequency Vibration on Delayed Onset Muscle Soreness and Resulting Stiffness as Measured by Shear-Wave Elastography. - Jones GC; Blotter JD; Smallwood CD; Eggett DL; Cochrane DJ; Feland JB (MDPI (Basel, Switzerland), 2021)
This study utilized resonant frequency vibration to the upper body to determine changes in pain, stiffness and isometric strength of the biceps brachii after eccentric damage. Thirty-one participants without recent resistance training were randomized into three groups: a Control (C) group and two eccentric exercise groups (No vibration (NV) and Vibration (V)). After muscle damage, participants in the V group received upper body vibration (UBV) therapy for 5 min on days 1-4. All participants completed a visual analog scale (VAS), maximum voluntary isometric contraction (MVIC), and shear wave elastography (SWE) of the bicep at baseline (pre-exercise), 24 h, 48 h, and 1-week post exercise. There was a significant difference between V and NV at 24 h for VAS (p = 0.0051), at 24 h and 1-week for MVIC (p = 0.0017 and p = 0.0016, respectively). There was a significant decrease in SWE for the V group from 24-48 h (p = 0.0003), while there was no significant change in the NV group (p = 0.9341). The use of UBV resonant vibration decreased MVIC decrement and reduced VAS pain ratings at 24 h post eccentric damage. SWE was strongly negatively correlated with MVIC and may function as a predictor of intrinsic muscle state in the time course of recovery of the biceps brachii.
Keywords: biceps; delayed onset muscle soreness; eccentric; elastography; recovery; shear-wave; skeletal muscle; vibration; whole-body; Elasticity Imaging Techniques; Exercise; Humans; Isometric Contraction; Muscle Strength; Muscle, Skeletal; Myalgia; Vibration